2009
DOI: 10.1371/journal.pgen.1000536
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Exonic Copy Number Variants in a Family-Based Study Point to Novel Autism Susceptibility Genes

Abstract: The genetics underlying the autism spectrum disorders (ASDs) is complex and remains poorly understood. Previous work has demonstrated an important role for structural variation in a subset of cases, but has lacked the resolution necessary to move beyond detection of large regions of potential interest to identification of individual genes. To pinpoint genes likely to contribute to ASD etiology, we performed high density genotyping in 912 multiplex families from the Autism Genetics Resource Exchange (AGRE) coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
326
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(340 citation statements)
references
References 55 publications
11
326
1
2
Order By: Relevance
“…[17][18][19][20] Other citations involving 1q21.1 duplication cases were also assessed. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Cases of 1q21.1 duplication in GeneReviews (http://www.ncbi.nlm. nih.gov/books/NBK52787) and the four references provided therein 1,2,10,25 were reviewed as well, but no new subjects or phenotypic data were identified.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20] Other citations involving 1q21.1 duplication cases were also assessed. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Cases of 1q21.1 duplication in GeneReviews (http://www.ncbi.nlm. nih.gov/books/NBK52787) and the four references provided therein 1,2,10,25 were reviewed as well, but no new subjects or phenotypic data were identified.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
“…3,35 We systematically reviewed 28 primary reports identified and their accompanying supplemental materials to identify unique individuals and abstract as much information as possible on each subject. 1,2,[5][6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Any subjects with 1q21.1 duplications that were not 1.0-5.0 Mb (Figure 1) in size were excluded, 12,31 allowing us to include atypical variants that were larger or smaller than the standard duplication classes used in our analyses. We documented the ascertainment criteria, country of origin, authors, and the demographic, clinical, and genotypic characteristics of subjects in different studies, and used these variables to attempt to identify duplicate cases reported in two or more papers.…”
Section: Materials and Methods Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Recent studies have demonstrated that ASDs can be caused by rare, highly penetrant point mutations, deletions, duplications and larger chromosomal abnormalities that can either arise de novo or be inherited. [3][4][5][6][7][8][9] Known monogenic disorders account for 2-5% of syndromic cases; fragile X syndrome is usually the most common cause, followed by PTEN macrocephaly syndrome and tuberous sclerosis, each accounting for o1% of individuals with ASD. 1,10 Large copy number variants (CNVs) are found in 5-10% of autistic patients, especially in those with syndromic ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Rare copy number variants (CNVs) have a role in the etiology of tetralogy of Fallot, sporadic epilepsy syndromes or autism. [6][7][8] In patients with sporadic aortic aneurysms and dissections rare CNVs were identified that disrupt genes involved in vascular smooth muscle function. 9 The current study was the first analysis of CNVs in CeAD.…”
Section: Introductionmentioning
confidence: 99%